Artificial Intelligence and Academic Integrity in Islamic Higher Education: Exploring Ethical Challenges among Islamic Education Students - Rahmatul Azizah; Riza Wardefi (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
The purpose of this study is to explore the ethical challenges associated with the use of Artificial Intelligence (AI) in the academic activities of Islamic Education (PAI) students in Islamic higher education and to examine the strategies and constraints involved in addressing these challenges. The study responds to the rapid adoption of generative AI tools in higher education, which has raised concerns regarding academic integrity, critical thinking, and the preservation of Islamic educational values. This research employed a qualitative case study design conducted at the Islamic Education Study Program of Universitas Negeri Padang. Data were collected through semi-structured interviews with ten PAI students and two lecturers, complemented by participant observation and document analysis. The data were analyzed using the interactive model of Creswell and Poth, strengthened by thematic analysis and validated through source and method triangulation. The findings reveal five interrelated ethical challenges: (1) students’ dependency on AI, (2) declining critical thinking skills, (3) reduced learning autonomy, (4) plagiarism and academic integrity concerns, and (5) the inaccuracy of AI-generated information. Efforts to address these challenges include independent verification of AI outputs, the use of alternative scholarly sources, assessment redesign, and contextual case-based learning. However, their effectiveness remains constrained by the absence of formal institutional policies, diverse understandings of academic ethics, and limited collaboration among stakeholders. The originality of this study lies in the development of an Islamic Values-Based AI Ethics Framework that integrates AI literacy, academic integrity, institutional governance, and the Islamic principles of ṣidq, amanah, and thalab al-‘ilm. This study contributes to the growing discourse on ethical AI adoption by providing a contextually grounded framework for promoting responsible AI use in Islamic higher education.